Utilization of green inhibitors as a sustainable corrosion control method for steel in petrochemical industries: A review - Alao, Alice Osheiza; Popoola, Abimbola Patricia; Dada, Modupeola Oluwaseun; Sanni, Omotayo (Frontiers in Energy Research, 2023)
Infrastructure upgrades in the energy sector are encouraged to satisfy the expanding world’s energy needs, including innovation, consumption, production, and transportation. Thus, steel has been an extensively used construction material, particularly for pipelines and oil wells. However, in their application, every step of the production cycle results in the corrosion of metal parts. One of the simplest and most active ways to inhibit steel from corroding, especially in acidic situations, is to use a corrosion inhibitor. Synthetic organic compounds have been used successfully as corrosion inhibitors in the gas and oil industry. However, their use is today restricted and controlled due to their toxicity, environmental harm, and growing concern about the preservation of ecosystems. This has necessitated the present trend of searching for and developing green inhibitors that are environmentally benign, non-toxic, biodegradable, and low in cost. Corrosion inhibitor develops a shielding layer on the metal surface. Corrosion is avoided by a thin coating that has been adsorbed on the metal surface, which keeps the metal isolated from its surroundings. Several researchers have reported on the success of green inhibitors for steel corrosion protection, particularly in acidic environments. However, the use of green inhibitors still leaves several questions about inhibitor formulation, content, and adsorption mechanisms to be answered. Therefore, based on provided experimental results and an explanation of their inhibitory action, the use of green inhibitors (especially organic inhibitors) for the prevention of pipeline steel corrosion in various grades is studied in this review. Both the identified drawback and the projected future trend have also been highlighted.